Contact behaviour of a sliding rubber element - Sextro, Walter; Moldenhauer, Patrick; Wangenheim, M; Lindner, Markus; Kröger, Matthias (Analysis and Simulation of Contact Problems)
Friction occurs in the contact between tyre and road. The friction of rubber material on dry surfaces is dominated by hysteresis and adhesion effects. Hysterisis friction is characterised by the energy dissipation within the visco-elastic material, which is caused by its deformation while passing the surface roughness. Hysteresis effects are modelled by an extended linear visco-elastic material with several Maxwell elements. The development of a model in the time domain allows to consider nonlinear effects. Additionally temperature effects are taken into account based on the WLF-transformation. Adhesion forces originate from molecular bindings between the contact partners. This effect is simulated by applying a modified model of Achenbach on real surfaces. The temperature distribution within the friction contact region is investigated experimentally as well. Furthermore global stick-slip vibrations of a rubber block element are investigated using a global contact model. Numerical results are compared with experiments performed on a tribometer test rig.

Energy harvesting with piezoelectric Elements - Twiefel, Jens; Hemsel, Tobias; Kauczor, Christopher (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Model-based design of piezoelectric energy harvesting systems
In the design process of energy harvesting systems based on piezoelectric elements, achievable energy output is the most interesting factor. To estimate this amount a priori manufacturing of prototypes a mathematical model is very helpful. Within this contribution we will introduce a model based on electro-mechanical circuit theory. Its parameters are identified by measurements and the model is validated by comparison to experimental results. The model is designed to support the development-engineer in the dimensioning of energy harvesting units to specific application demands. Two main challenges in device design are investigated with the mathematical model: influence of the ambient excitation frequency, and influence of the load impedance. Typically, the equivalent model approach delivers models for piezoelectric elements that are driven in resonance by electrical excitation. In the case of energy harvesting the piezoelectric elements are excited mechanically and most often non-resonant. Thus, we first set up a mechanical equivalent model for base excited systems. In first approximation it represents an energy harvesting unit around one resonance frequency. The model is expandable for a wider frequency range using the superpositioning of multiple circuits. From the viewpoint of optimum energy transformation between mechanical and electrical energy it is favorable to drive piezoelectric elements at resonance or anti-resonance. Thus, an energy harvesting system should be tuned to the excitation frequency.

Non-resonant piezoelectric motors driven in audible frequency range - Wilmanns, S; Nakamura, K; Mracek, Maik; Hemsel, Tobias (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Piezoelectrics in dental tools - Zhou, W; Fu, Bo; Hemsel, Tobias; Wallaschek, Jörg (Proceedings of 2nd International Workshop on Piezoelectric Materials and Applications in Actuators)

Proceedings of the Workshop on Model Driven Development of Advanced User Interfaces, satellite of the MoDELS 2006 conference

Fairness Considerations in Replication and Placement Strategies for large Documents in heterogeneous Content Delivery Networks - Loeser, Christoph; Schomaker, Gunnar; Schubert, Matthias; Schattkowsky, Tim (Proceedings of the 5th International Conference on Networking (ICN 2006), Morne (Mauritius))

Secure Storage for Physically Exposed Web- and Application Servers - Schattkowsky, Tim; Förster, Alexander; Loeser, Christoph (Proceedings of the 5th International Conference on Networking (ICN 2006), Morne (Mauritius))

Using UML Activities for System-on-Chip Design and Synthesis - Schattkowsky, Tim; Hendrik Hausmann, Jan; Engels, Gregor (Proceedings of the International Conference on Model Driven Engineering Languages and Systems (MoDELS 2006), Genova (Italy))

Workshop Report: Model Driven Development of Advanced User Interfaces (MDDAUI) - Pleuß, Andreas; Van den Bergh, Jan; Sauer, Stefan; Hußmann, Heinrich (Satellite Events at the MoDELS 2005 Conference, MoDELS 2005 International Workshops, Doctoral Symposium, Educators Symposium, Revised Selected Papers, Montego Bay (Jamaica))

Generating Instance Models from Meta Models - Ehrig, Karsten; Taentzer, Gabriele; Küster, Jochen; Winkelmann, Jessica (Proceedings of the conference on Formal Methods for Open Object-Based Distributed Systems (FMOODS 2006), Bologna (Italy))

Combining Analysis of Unstructured Workflows with Transformation to Structured Workflows - Hauser, Rainer; Friess, Michael; Küster, Jochen; Vanhatalo, Jussi (Proceedings of the 10th IEEE International Enterprise Distributed Object Computing Conference (EDOC 2006))

Teaching UML Is Teaching Software Engineering Is Teaching Abstraction - Engels, Gregor; Hendrik Hausmann, Jan; Lohmann, Marc; Sauer, Stefan (Proceedings of the Satellite Events at the MoDELS 2005 Conference, Montego Bay (Jamaica))
As the Unified Modeling Language (UML) has by now seen widespread and successful use in the software industry and academia alike, it has also found its way into many computer science curricula. An outstanding advantage of teaching UML is that it enables an illustration of many crucial concepts of software engineering, far beyond its concrete notation. Most important among these concepts is that of abstraction. We present a course design which demonstrates the use of UML as a vehicle for teaching such core concepts of software engineering. Multimedia elements and tools help to efficiently convey the courses message to the students.

Model-Driven Monitoring: An Application of Graph Transformation for Design by Contract - Engels, Gregor; Lohmann, Marc; Sauer, Stefan; Heckel, Reiko (Proceedings of the 3rd International Conference on Graph Transformation (ICGT 2006), Natal (Brazil))
The model-driven development (MDD) approach for constructing software systems advocates a stepwise refinement and transformation process starting from high-level models to concrete program code. In contrast to numerous research efforts that try to generate executable function code from models, we propose a novel approach termed model-driven monitoring. Here, models are used to specify minimal requirements and are transformed into assertions on the code level for monitoring hand-coded programs during execution. We show how well-understood results from the graph transformation community can be deployed to support this model-driven monitoring approach. In particular, models in the form of visual contracts are defined by graph transitions with loose semantics, while the automatic transformation from models to JML assertions on the code level is defined by strict graph transformation rules. Both aspects are supported and realized by a dedicated Eclipse plug-in.

A Pattern-driven Development Process for Quality Standard-conforming Business Process Models - Förster, Alexander; Schattkowsky, Tim; Engels, Gregor; Van Der Straeten, Ragnhild (IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC 2006), Brighton (UK))

Model-driven Monitoring: Generating Assertions from Visual Contracts - Lohmann, Marc; Engels, Gregor; Sauer, Stefan (Proceedings of the 21st IEEE International Conference on Automated Software Engineering (ASE 06), Tokyo (Japan))
The Visual Contract Workbench is a tool that supports model-driven development of software systems by lifting the Design by Contract idea, which is usually used at the code level, to the model level. It uses visual contracts for graphically specifying the pre- and post-conditions of an operation. Java classes with JML (Java Modeling Language) assertions are generated from visual contracts to facilitate automatic monitoring of the correctness of the programmer's implementation.

Industrielle Fallstudie: Einsatz visueller Kontrakte in serviceorientierten Architekturen - Engels, Gregor; Güldali, Baris; Juwig, Oliver; Lohmann, Marc; Richter, Jan-Peter (Proceedings of the conference on Software Enginneering, Fachtagung des GI Fachbereichs Softwaretechnik (SE 2006), Leipzig (Germany))
Serviceorientierte Architekturen (SOA) erlauben eine schnelle und kosteneffiziente Bereitstellung unterschiedlicher Funktionalitäten zur Unterstützung der Geschäftsprozesse eines Unternehmens. Dazu werden fachliche Funktionalitäten in Form von Enterprise Services zur Verfügung gestellt. Die hohe Zahl von Enterprise Services erfordert eine geeignete semantische Beschreibung zu deren effizienten Verwaltung. Zur semantischen Beschreibung von Enterprise Services sowie zur Formulierung von Suchanfragen ist an der Universität Paderborn die Methode der visuellen Kontrakte entwickelt worden. Das Papier stellt die Ergebnisse der ersten Phase einer umfangreichen industriellen Fallstudie zur Evaluation der praktischen Anwendbarkeit visueller Kontrakte im Kontext einer SOA vor.

Semantische Beschreibung von Enterprise Services – Eine industrielle Fallstudie - Lohmann, Marc; Richter, Jan-Peter; Engels, Gregor; Güldali, Baris; Juwig, Oliver; Sauer, Stefan

Adaptations of Renewable Energy Policies to unstable macroeconomic situations – Case study: Wind power in Brazil - Kissel, J.; Krauter, Stefan (Energy Policy)

Optical modelling and simulation of PV module encapsulation to improve structure and material properties for maximum energy yield - Krauter, Stefan; Grunow, Paul (Proceedings of the 4th World Conference on Photovoltaic Energy Conversion (Joint congress of IEEE/PVSEC/EUPVC), Waikoloa, Hawaii (USA), 8.–12. Mai 2006, S. 2133–2137)